HEALTH LITERACY: A PREREQUISITE FOR POPULACE WELFARE - Nalini R; Alamelu R; Amudha R; CRESENTA SHAKILA MOTHA L (Asian Journal of Pharmaceutical and Clinical Research, 2016)
ABSTRACT The objective of this study is to know about the significance of health literacy awareness among the public. Health literacy is a strategy to empower the control of people over their own health and capacity to inquire about the health information to take decisions regarding the health issues. People must increase their health literacy with quality and understanding information. The impact of less health literacy rates is errors in medication, inferior health position, increased hospitalizations, and increased cost of health care. The competency to make health decisions in daily life, at work life, in health-care system, and in emergency situations will determine the health literacy. The health literacy means the attaining the level of knowledge, individual skills and confidence to arrive decisions to enhance individual and societal health by altering lifestyles and livelihood. Low literacy level has an impact on the health status of the people by restricting the individual, social and cultural progress thereby impede the progress of health literacy. The health literacy can be regarded as a capacity needed to be familiar with sources of health information and use them by retrieving the information. The accessibility of quality information, its applicability in a required situation, analyzing, understanding, and utilizing of information is necessary for taking efficient health decisions. Keywords: Health literacy, Empowerment strategy, Health decisions and health care system.